2021
DOI: 10.3389/fcvm.2021.704281
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Drugs Effects on Blood Pressure

Abstract: Individuals suffering from depressive disorders display a greater incidence of hypertension compared with the general population, despite reports of the association between depression and hypotension. This phenomenon may depend, at least in part, on the use of antidepressant drugs, which may influence blood pressure through different effects on adrenergic and serotoninergic pathways, as well as on histaminergic, dopaminergic, and cholinergic systems. This review summarizes extant literature on the effect of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 222 publications
1
37
0
1
Order By: Relevance
“…Imipramine inhibits ASMase by reuptake of monoamines such as norepinephrine, dopamine, and serotonin. Additionally, imipramine has anti-inflammatory and antiapoptotic effects [ 47 , 48 ]. In this study, we found that imipramine administration reduced the number of degenerating neurons, oxidative damage, dendritic loss, glial activation, and cognitive dysfunction ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Imipramine inhibits ASMase by reuptake of monoamines such as norepinephrine, dopamine, and serotonin. Additionally, imipramine has anti-inflammatory and antiapoptotic effects [ 47 , 48 ]. In this study, we found that imipramine administration reduced the number of degenerating neurons, oxidative damage, dendritic loss, glial activation, and cognitive dysfunction ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning as well that the link between major depression and certain behavioral factors such as increased rates of smoking and physical inactivity might also contribute to the increased risk of hypertension among depressed individuals [ 23 ]. When treating depression, clinicians should carefully assess the blood pressure status since antidepressant medications might affect the blood pressure [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depression might increase the risk for uncontrolled hypertension [ 8 ]. When treating depression, clinicians should also carefully assess the blood pressure status since antidepressant medications might affect the blood pressure [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Abdel-Bakky et al, 2021;McCarron et al, 2021). Considering SSRIs, prolonged bleeding time, and, when used during pregnancy, heart defects and pulmonary hypertension in newborns have been observed (Berard et al, 2017;Calvi et al, 2021). For newer medications, such as those approved by the FDA for treatment of MDD, ansofaxine (potential triple reuptake inhibitor of serotonin, norepinephrine, and dopamine, approved in 2019) or vilazodone (a selective serotonin reuptake inhibitor and serotonin 5-HT1A receptor partial agonist, approved in 2021), the side effects are very similar to traditional antidepressants.…”
Section: The Antidepressants Used In the Clinicmentioning
confidence: 99%